2014
DOI: 10.1099/ijs.0.063255-0
|View full text |Cite
|
Sign up to set email alerts
|

Liberibacter crescens gen. nov., sp. nov., the first cultured member of the genus Liberibacter

Abstract: The Gram-stain-negative, rod-shaped bacterial isolate BT-1T is the closest relative to the genus ‘Candidatus Liberibacter ’ cultured to date. BT-1T was recovered from the phloem sap of a defoliating mountain papaya in Puerto Rico. The BT-1T 16S rRNA gene sequence showed that strain BT-1T is most closely related to members of the genus ‘Ca. Liberibacter ’ sharing 94.7 % 16S rRNA gene sequence si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 29 publications
2
84
0
2
Order By: Relevance
“…Liberibacter solanacearum' ZC1, the causal agent of tomato psyllid yellows and potato zebra chip, and found a total of 207 genes of known functions and 238 hypothetical genes of unknown function unique to Lcr, some of which could contribute to its ability to grow in vitro. The CaL species lost the ability to synthesize proline, phenylalanine, tryptophan, cysteine, tyrosine and histidine as well as components of several systems that could compromise their ability to sense and adjust to environmental fluctuations, such as two-component regulatory systems, the stringent response, and an alternate cytochrome pathway [59]. In addition, Lai et al [62] using genome-wide transposon mutagenesis identified 314 protein-coding genes required for Lcr BT-1 growth in BM7 medium.…”
Section: 'Candidatus Liberibacter'mentioning
confidence: 99%
See 2 more Smart Citations
“…Liberibacter solanacearum' ZC1, the causal agent of tomato psyllid yellows and potato zebra chip, and found a total of 207 genes of known functions and 238 hypothetical genes of unknown function unique to Lcr, some of which could contribute to its ability to grow in vitro. The CaL species lost the ability to synthesize proline, phenylalanine, tryptophan, cysteine, tyrosine and histidine as well as components of several systems that could compromise their ability to sense and adjust to environmental fluctuations, such as two-component regulatory systems, the stringent response, and an alternate cytochrome pathway [59]. In addition, Lai et al [62] using genome-wide transposon mutagenesis identified 314 protein-coding genes required for Lcr BT-1 growth in BM7 medium.…”
Section: 'Candidatus Liberibacter'mentioning
confidence: 99%
“…Recently, the bacterial isolate BT-1 was recovered in pure culture from the phloem sap of defoliating mountain papaya (Carica stipulata × C. pubescens) in Puerto Rico and shown to be closely related to CaLam and CaLas based on similarity of 16S rDNA and conserved protein sequences as well as on genome-wide ANI analysis [58,59]. The isolation and genome sequencing of this isolate, classified as Liberibacter crescens (Lcr), allowed for the first time a comprehensive description of the morphological, biochemical, and physiological characteristics of the genus Liberibacter [59].…”
Section: 'Candidatus Liberibacter'mentioning
confidence: 99%
See 1 more Smart Citation
“…The malformed names 'Candidatus Liberobacter asiaticum' and 'Candidatus Liberobacter africanum' [5] were later corrected to 'Candidatus Liberibacter asiaticus' and 'Candidatus Liberibacter africanus' [6]. After a member of the group was brought into pure culture, the genus name Liberibacter was validly published [7].…”
mentioning
confidence: 99%
“…Liberibacter crescens (Lcr), as the only cultured species within the liberibacters, is the first representative of the new genus Liberibacter to be validly published and named [35]. This species has been isolated from expressed sap of a defoliating mountain papaya in Puerto Rico [35].…”
Section: Introductionmentioning
confidence: 99%